Assessment and Content Analysis of Highly Cited Publications in Reference Services - Zia, Sadaf; Mushtaq, Muzamil (Journal of Data Science, Informetrics, and Citation Studies)
The study is aimed to assess the top highly cited publications in the field of reference services. The data was extracted from Scopus database by searching “reference service” phrase in the document search tab and limited to social science subject area and journal sources type. The results were confined to LIS journals in source titles which retrieved 1861 number of articles from which top 50 cited articles have been selected for conducting the present study. A content analysis of these top 50 highly cited publications have been performed in order to assess their quality. The parameters of assessment were the authors, year of publication, top contributing countries, institutions and journals, year wise distribution and scores of contributing journals, subject areas, methodology, and number of references. In addition, literature review, hypotheses, research questions, the variations in findings and conclusion have also been studied. It was found from the analysis of results that the highly cited papers include single authorship pattern and were mostly contributed by USA. The majority of the cited articles have academic libraries and Information Technology as the research subject area and adopted survey method to conduct their studies. Reference Services Review was found as the top most contributing journal. The analysis of the results further shows that the maximum number of the cited papers is without literature review and research questions whereas not a single publication was found with a hypothesis. The maximum numbers of the highly cited publications were found without headings of findings, discussion and future suggestions but mentioned the conclusion separately and have included references in the range of 11-20.
Keywords: Content Analysis; Citations; LIS Journals; Highly cited Publications; Reference Service; Scopus.